Total productive maintenance and manufacturing performance: Does technical complexity in the production process matter? - Mad Lazim, Halim; Salleh, Mohamed Najib; Subramaniam, Chandrakantan; Othman, Siti Norezam (IACSIT Press, 2013)
This paper intends to discuss some findings from a study of TPM practices in manufacturing organizations in Malaysia. Total productive maintenance (TPM), a resource-emphasized approach moves the paradigm of maintenance by putting emphasis on total employee involvement in the maintenance activities.We studied the relationship between TPM practices and manufacturing performance. We investigated the moderating effect of the level of technical complexity in the production process in the TPM practices and manufacturing performance relationships as well. Significant relationships were found between TPM practices and cost.We also found the moderating effect of technical complexity in the production process on the relationship between TPM practices and manufacturing performance.